CYBER-SOCIAL SOCIETY: THE NEWEST RHIZOME - Kleshnia, Hanna (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2022)
Introduction. Philosophical reflection on the world is essential as an attempt to identify markers of society’s behavior in a reality that is increasingly being portrayed as a simulacrum of chaos. The theoretical basis of the article was sociological and cultural-philosophical studies of D. Bell, A. Buhl, M. Weinstein, M. Castells, A. Crocker, J.-F. Lyotard, M. Maffesoli, J. Nesbitt, M. Paetau, E. Toffler, and others. The aim and tasks are identifying the features of the social reality of modern society and their philosophical understanding in the paradigm of postmodern culture. Research methods area set of philosophical and general scientific approaches and methods: systematics, objectivity, convergence from the abstract to the concrete. The article uses the interdisciplinary synergetic methodology to understand the dynamics of self-organization in the network society. Research results. Lack of stable principles and norms, socio-cultural isolation, and historical relativity are the main characteristics of postmodern culture, which allows us to define the social reality as a kaleidoscope of events and a disordered system, which is a multifaceted set of loosely connected parts, fragments, and elements. And coherence and integrity are fundamentally rejected by this cultural paradigm because it is based on movement, change, and deformation. The information society has not been fully realized, which encourages the search for alternative models of explanation of modern social reality. The emphasis in the "new" information society is not on the growing role of knowledge but on the development of communication practices. All ideas of modern society as a virtual society are permeated by the idea of transferring basic social practices - communication, exchange, work, production - to the computer-generated alternative (virtual) space, or cyberspace. Today, social practices transferred to the virtual space acquire the status of real, not "parallel", similar to the real thing. The virtual world becomes the environment of "being" and the embodiment of simulacra. Discussion. Hungarian researchers B. Kolanyi, S. Molnar and L. Shekeli state that networks have become one of the most fundamental elements of human civilization, which absence makes it impossible to imagine modern society. They believe that traditional family, neighborly and friendly ties are gradually becoming less important than networking ones. Umberto Eco was one of the first to discover the features of the conditional Middle Ages in the "offline" space of society. M. Maffesoli describes the direction of social development as an ingress, a concept based only on the present because it lives in the moment. Соnclusion. Structured in the way of horizontal interaction, social virtual, and "offline" networks become open to social engineering, social planning and forecasting on-line. Complementing self-organizational processes, these procedures reveal the transmission of the socio-cultural potential of global information networks into social reality and embody a virtual prototype of reality. Thus, there is an openness of postmodern (hyper industrial) society and its cultural determinants to the possible manipulation of both classical (socio-political) and the latest (information and network) methods.